Age, depositional history and tectonics of the Indo-Myanmar Ranges, Myanmar - Naing, TT; Robinson, S; Searle, M; Morley, C; Millar, I; Green, O; Bown, P; Danelian, T; Petrizzo, M-R; Henderson, G (Geological Society, 2023)
The Indo-Myanmar Ranges make up an enigmatic mountain belt occupying a complex tectonic zone in western Myanmar, extending from the northern continuation of the active Sunda–Andaman arc into the eastern Himalayan Syntaxis. The Indo-Myanmar Ranges are part of an accretionary forearc basin–arc complex that includes the Central Myanmar Basin and the Wuntho–Popa Arc to the east. New biostratigraphic, petrological and detrital zircon U–Pb age data are presented and used to test and refine the divergent tectonic models that have been proposed for western Myanmar. These data suggest that: (1) the Upper Triassic Pane Chaung Formation was originally deposited adjacent to the NE Indian continental margin within northern Gondwana during the Late Triassic; and (2) the Upper Cretaceous–Paleogene rocks of the Indo-Myanmar Ranges were mainly derived from the Wuntho–Popa Arc and Inner Belt, with a subordinate input from a crustal source, potentially from the Naga metamorphic-type Paleozoic basement. The Kalemyo Ophiolite has an Early Cretaceous age similar to the ages of ophiolites in the Indus–Yarlung Tsangpo Suture Zone, south Tibet and Nagaland, reinforcing the hypothesis that they were once part of the same Neotethyan ocean floor.